Market Opportunities and Marketing Strategies in Layer Chicken Farming Business (Case Study: Egg Business in Bengkol Subdistrict, Manado City, North Sulawesi) - Kaunang, Stella T.; Dewi, Elisabeth H.; Polan, Thresia S.; Uguy, Wempie (Formosa Journal of Science and Technology, 2024)
Livestock farming is one of the crucial aspects of agricultural development. The role of the livestock subsector in agricultural development is significant, with one of the important products being the production of eggs and broiler chickens. Egg consumption in Indonesia has been increasing over the years, leading to an increase in egg production. This research aims to formulate development strategies using a descriptive analysis method. Data collection is done through questionnaires, interviews, and a review of literature related to the research. Data analysis utilizes the SWOT analysis method (Strengths, Weaknesses, Opportunities, Threats) to identify internal factors (strengths and weaknesses) and external environmental factors (opportunities and threats). The results of this analysis are then depicted in the SWOT quadrant and interpreted in the SWOT matrix. The research findings indicate an identification value of 3.3 for internal factors and 3.23 for external factors, suggesting that the development strategy for Ellen Farm's laying hen in Bengkol Village, Mapanget District, falls into quadrant I. This implies an intensive market strategy, including market penetration, market development, and product development.